GAMIFICATION-BASED ADAPTIVE LEARNING USING FUZZY ALGORITHMS IN SMART LEARNING ENVIRONMENTS - Fahrijal Pukeng, Ahmad
Education is a critical aspect in the development of quality and competitive human resources. In a smart learning environment, students' success in understanding and mastering learning materials plays an important role in measuring learning progress and identifying individual learning needs. Measuring the success of students' level of mastery and understanding can be done in several ways such as assignments, exams, and tests or assessments. However, there are several obstacles in this learning activity, namely static assessment conditions that are less adaptive, difficulty identifying student abilities and feedback that is not given to the development of student understanding which results in a lack of student motivation in learning. This research develops a gamification-based adaptive learning application using quiz-based fuzzy algorithms, to provide positive reactions and new experiences to students through interactive learning that is not monotonous utilizing text, image and sound elements, so that it can increase learning motivation, knowledge and student learning effectiveness from the point of view of student interaction and involvement. This research uses DRM (Design Research Methodology) as the research approach, by adopting the SLEEG (Smart Learning Environment Establishment Guideline) method using the ADDIE (Analyze, Design, Develop, Implement, Evaluate) method as the development method. Application testing involved 141 respondents. Testing was conducted using pre-test and post-test methods, as well as a student perception survey by adopting the HMSAM (Hedonic-Motivation System Adoption Model) to see the impact of using the application on students from the point of view of reactions, increased knowledge and learning outcomes. The reaction evaluation results show that the use of gamification-based learning application using fuzzy algorithm has a positive impact on user motivation and engagement. In addition, the learning impact evaluation showed an increase in scores with a difference of 8.11 points for group B and a difference of 3.81 points for group A, indicating an increase in user scores after receiving adaptive learning treatment using the application.